A dor em pacientes sob cuidados paliativos: um estudo com equipe multiprofissional - Bezerra, Ana Hévila Marinho (2018)
Palliative care deals with a therapeutic approach based on the diagnosis of lifethreatening pathologies, which should have a multidisciplinary approach, focused on relieving the suffering of the patient, mainly regarding the symptom of pain. This dissertation was developed from the construction of two articles. The review article entitled “Palliative care and pain: an integrative literature review” aimed to identify, in the scientific production on palliative care and pain, aspects related to the management and control of pain in patients without possibilities of cure, available in online journals in the Brazilian scenario, in the LILACS, BDENF and MEDLINE databases. The study sample was composed of twenty-seven articles; and the analyzed empirical material gave rise to two thematic categories: Management and control of pain in palliative care; Multidisciplinary team in the relief pain of patients in palliative care. The second article, with an exploratory nature and a qualitative approach, entitled “Pain in patients undergoing palliative care: behavior of the multidisciplinary team” aimed to investigate the behavior of the multidisciplinary team in the management of pain in patients undergoing palliative care. The study population was composed by professional nurses, physiotherapists and physicians, totaling a sample of twenty professionals. Data collection was performed from a recorded interview, and the empirical material was analyzed by the content analysis technique. The analysis of data gave rise to three thematic categories: Strategies for identifying and evaluating pain in patients undergoing palliative care; Behavior of the multidisciplinary team in the relief of pain of patients undergoing palliative care; and Weaknesses found in multidisciplinary assistance to patients undergoing palliative care. Accordingly, the studies developed in this dissertation contribute to improving clinical practice and boosting the development of new studies, based on a reflection by the professionals about the need to identify and control pain, establish clinical assistance-related protocols and appreciate the multidisciplinary view.